2010
DOI: 10.1002/cphc.200900935
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Magnetic Exchange Interactions and NiSNi Bond Angles in Polynuclear Nickel(II) Complexes

Abstract: The ability of bridging thiophenolate groups (RS -) to transmit magnetic exchange interactions between paramagnetic Ni(II) ions has been examined. Specific attention was paid to complexes with large Ni-SR-Ni angles. For this purpose, dinuclear [Ni2Land trinuclear [Ni3L 2 (OAc)2][BPh4]2 (3), where H2L 1 and H2L 2 represent 24-membered macrocyclic amino-thiophenol ligands, were prepared and fully characterized by IR-and UV-vis spectroscopy, X-ray crystallography, static magnetization M measurements and high-fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…3. A transfer of the spectral weight to lower magnetic field at low temperatures revealed a negative axial magnetic anisotropy of the molecule (parameter D < 0) in both complexes [11,4], in accord with the self-orientation of the particles during measurements in a high magnetic field and the presence of an "easy" axis of anisotropy. …”
Section: Hf-esr Spectramentioning
confidence: 68%
See 1 more Smart Citation
“…3. A transfer of the spectral weight to lower magnetic field at low temperatures revealed a negative axial magnetic anisotropy of the molecule (parameter D < 0) in both complexes [11,4], in accord with the self-orientation of the particles during measurements in a high magnetic field and the presence of an "easy" axis of anisotropy. …”
Section: Hf-esr Spectramentioning
confidence: 68%
“…1 and 2. The relation between the axial ZFS parameter, D, and the magnetic anisotropy gap, ∆, is: [4,5] …”
Section: Discussionmentioning
confidence: 99%
“…A previous high-field EPR study has shown that the D values for Ni II 2 complexes supported by the N 6 S 2 macrocycle have a negative sign and are on the order of 0.5-1.0 cm -1 . [22] Nevertheless, the value of J is unambiguous and represents an accurate measure of the magnetic coupling in these complexes.…”
Section: Wwwzaacwiley-vchdementioning
confidence: 99%
“…In contrast to H 2 L1, which supports mono-and dinuclear Ni II complexes, the ligand H 2 L3 was found to form a trinuclear Ni II complex, due to participation of the 2-hydroxyethyl substituents in the coordination of the metal ions. [15] Herein, the synthesis of the ligands H 2 L4 and H 2 L5 carrying pendant 2-methoxyethyl substituents [16] is described and their ability to form mono-and dinuclear Ni complexes is demonstrated. The crystallographic analyses of two complexes provide insights into the effects of the conversion of the 2-hydroxyethyl to 2-methoxyethyl groups on the structural features.…”
Section: Introductionmentioning
confidence: 99%